2017
DOI: 10.1097/aln.0000000000001509
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Disrupts the Local and Global Efficiencies of Large-scale Brain Networks

Abstract: Background A clear understanding of the neural basis of consciousness is fundamental to research in clinical and basic neuroscience disciplines and anesthesia. Recently, decreased efficiency of information integration was suggested as a core network feature of propofol-induced unconsciousness. However, it is unclear whether this finding can be generalized to dexmedetomidine, which has a different molecular target. Methods Dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 50 publications
8
60
0
Order By: Relevance
“…Dexmedetomidine is a highly selective a2 adrenergic agonist and is unique among currently 52 available anesthetics, most of which are known to act at multiple receptors in the central nervous 53 system. A recent neuroimaging study suggests that dexmedetomidine significantly reduces 54 information transfer in the local and global brain networks in humans (Hashmi et al, 2017), 55 consistent with the effect of propofol (Monti et al, 2013). Functional disconnection between brain 56 regions is a possible mechanism suggested for dexmedetomidine-induced unconsciousness (Akeju 57 et al, 2014a;Song et al, 2017).…”
Section: Abstract 18mentioning
confidence: 75%
“…Dexmedetomidine is a highly selective a2 adrenergic agonist and is unique among currently 52 available anesthetics, most of which are known to act at multiple receptors in the central nervous 53 system. A recent neuroimaging study suggests that dexmedetomidine significantly reduces 54 information transfer in the local and global brain networks in humans (Hashmi et al, 2017), 55 consistent with the effect of propofol (Monti et al, 2013). Functional disconnection between brain 56 regions is a possible mechanism suggested for dexmedetomidine-induced unconsciousness (Akeju 57 et al, 2014a;Song et al, 2017).…”
Section: Abstract 18mentioning
confidence: 75%
“…The regression analysis of the effects of the covariates was limited in power by the sample size and by the presence of correlated predictors: (a) etiology and DOC duration, (b) sedation and diagnosis. It has been reported that dexmedetomidine reduces average brain connectivity strength in healthy individuals (Hashmi et al, ), although its effect on some aspects of brain connectivity was found to be smaller than that of propofol and non‐rapid‐eye‐movement sleep (Guldenmund et al, ). These results suggest that the effect of sedation may be significant in our context.…”
Section: Discussionmentioning
confidence: 99%
“…All epochs and channels with noise or non-physiological artifacts were visually identified and removed. We then band-pass filtered the cleaned EEG data into delta (1-4 Hz), theta (4-8Hz), alpha , and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency bands. Analysis of the alpha band were presented in the main body of the paper, while analyses of other frequency bands are included in the supplementary material.…”
Section: Electroencephalographic Acquisition and Preprocessingmentioning
confidence: 99%
“…Both electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) studies have shown that propofol-, sevoflurane-, and ketamine-induced unconsciousness induce a functional disconnection of anterior and posterior regions of the cortex [3][4][5][6][7][8], while propofol and sevoflurane also induce an anteriorization of alpha power from the occipital to the frontal cortex [9][10][11]. Graph theoretical analysis has demonstrated that global and topographic properties of brain networks are altered during anesthetic-induced unconsciousness [12][13][14][15][16]. While these advances have led to a clearer understanding of how anesthetic-induced unconsciousness creates inhospitable conditions for information processing and transfer [17], these measures describe whole-brain network processes rather than region-specific changes in brain functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation